Non-Tariff Barriers - the Achilles' Heel of Trade Policy Analyses - Taran Fæhn (Statistics Norway, Research Department, 1997)
This study demonstrates the quantitative, as well as the qualitative, role of non-tariff barriers (NTBs). The Norwegian nominal tariff and non-tariff barriers are identified and thoroughly quantified. Computations of effective rates of protection (ERP) show that NTBs entirely dominate tariffs as direct contributors to primary factor income, which again is an important determinant in allocation of resources among industries. The indirect input-output effects play a decisive role. This points to the importance of estimating the nominal trade barrier inputs properly; when a biased estimate is spread throughout the input-output system, not even the direction of the miscalculation will be easy to predict. In order to demonstrate the qualitative role, NTBs are categorised into price-oriented and quantity-oriented, respectively. ERP computations illustrate that the conclusions of policy analyses rely critically on the qualitative interdependency between quantity-oriented NTBs and other measures.
Keywords: C80; F13; L60; L70; 330; Non-tariff barriers; Trade policy; ERP computations.